PLATAFORMAS DIGITALES Y SU INCIDENCIA EN LA DIFUSIÓN DE LA INFORMACIÓN A LOS HABITANTES DEL CANTÓN EL EMPALME AÑO 2022. - Delgado Pérez, Jefferson Antonio (2023)
The main objective of this research work is to analyze the incidence of digital platforms in the dissemination of information to the inhabitants of the El Empalme canton, because in effect this has implied benefits by having greater access to the information present on the web, but at the same time it has become a complication because all kinds of information is disseminated on these platforms that are not easily distinguished as true or false, which has led administrators and users of these platforms to challenges in recognizing the information disseminated by these spaces, in addition to this, there is currently a gap in terms of access to technology because not all homes have Internet service. Therefore, the research is also focused on identifying the type of information most widely disseminated through digital platforms and on determining the influence on the opinions and decision-making of the inhabitants of the canton, for the development of this study a type of Field research in conjunction with quantitative and qualitative, also using analytical, interpretative and descriptive methods, for a better investigative result, it was decided to apply a structured survey to the inhabitants of the El Empalme canton and through the results obtained, propose strategies to improve the information quality disseminated through digital platforms to make it safer for the inhabitants.